Development of Kirchoff’s Law Drawing Tools to Improve Student’s Science Skills in Learning Process of Direct Flow Circuits - Ainun, Nur; Jefriyanto, Jefriyanto (Yayasan Gema Bina Nusantara, 2023)
This research develops a teaching tool for Kirchoff's law on the concept of direct current circuits, which is motivated by the minimal number of tools and the lack of tools available in schools as learning media and to improve science process skills. The development of the tool lies in replacing the input source with an adapter because the energy does not run out quickly, resulting in a more stable value. The research method used is development research from Akker with the type of development research model, which consists of introduction, prototype, summative evaluation, systematic reflection, and documentation. The purpose of this research is to test the feasibility, effectiveness and practicality of the developed teaching aids. The research subjects were 100 students from two classes. The instruments used were non-tests (guidelines for interviews, observations, and questionnaires) and multiple-choice tests. The results of the assessment of Kirchoff's legal aids were declared feasible, effective, and practical.